Authentic Leadership of Madrasah Heads in Realizing a Culture of Religious Moderation - Latifah, Ami; Patimah, Siti; Murtafiah, Nurul Hidayati (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
Islamic education has an important role in forming religious, tolerant, and inclusive students in the midst of the challenges of radicalism and social diversity. This study aims to analyze the leadership strategy of the head of Madrasah Aliyah Hidayatul Mubtadiin Jati Agung in internalizing the values of religious moderation, including the understanding of madrasah heads towards moderation in the local context, implementation strategies in the curriculum, school culture, and religious habits, parties involved as well as supporting and inhibiting factors, as well as the influence of strategies on the formation of a tolerant and inclusive madrasah culture. This study uses a qualitative method with a case study approach. Primary data was obtained from madrasah heads, teachers, education staff, and students, while secondary data was obtained from institutional documents, madrasah programs, disciplines, and activity documentation. The research was carried out at MA Hidayatul Mubtadiin Jati Agung, South Lampung. Data were collected through observation, in-depth interviews, and documentation, then analyzed using Miles et al.'s interactive model through data reduction, data presentation, and conclusion/verification. The results of the study show that madrasah heads understand religious moderation as a religious attitude that is balanced, tolerant, anti-violent, and relevant to local social diversity. The internalization strategy is carried out through the integration of moderation values in learning, strengthening school culture, religious habituation, teacher capacity development, and collaboration with religious leaders, KUA, FKUB, and the community. Supporting factors include the commitment of the madrasah head, teacher involvement, community support, and the religious culture of the madrasah, while the inhibiting factors include differences in student understanding, limited literacy moderation, and the influence of the external environment. This strategy has an impact on the formation of a madrasah culture that is more dialogical, tolerant, inclusive, and responsive to the prevention of radicalism.